Defense Logistics Management in Border Areas - Hermanto, Djamarel; Saragih, Herlina Juni Risma (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
This article thoroughly investigates the optimization of defense logistics management within national border areas, with a distinct focus on integrating a "soft power" approach. Border regions are inherently complex, characterized by extreme geographical conditions, challenging accessibility, and intricate socio-cultural dynamics, all of which demand the implementation of highly adaptive, efficient, and strategically nuanced logistics systems. Beyond its traditional function of facilitating the movement of goods and operational support, defense logistics is presented as a crucial mechanism for cultivating trust, actively supporting community well-being, and significantly enhancing regional stability. This qualitative research, conducted through an extensive literature review and descriptive-analytical analysis, meticulously analyzes various facets of logistics support systems—ranging from planning and procurement to efficient storage and diverse transportation methods—and examines various logistics distribution models, emphasizing the indispensable role of active local community involvement and robust cross-sectoral collaboration. The key findings unequivocally demonstrate that effective and strategically applied defense logistics is not merely foundational for robust military operations but also functions as a powerful catalyst for fostering positive civil-military relations, ultimately contributing to sustainable development, enhanced security, and enduring stability in these critical border regions.